Nanosecond Pulsed Laser‐Heated Nanocrystals Inside a Metal‐Organic Framework Matrix. Issue 6 (5th May 2022) - Niemeyer, Max; Bessel, Patrick; Rusch, Pascal; Himstedt, Rasmus; Kranz, Daniel; Borg, Hadir; Bigall, Nadja C.; Dorfs, Dirk
Abstract: Investigations on gold and gold‐zinc oxide nanocrystals encapsulated in a matrix of a metal‐organic framework (ZIF‐8) upon plasmonic heating with nanosecond laser pulses are presented. Irradiation of Au@ZIF‐8 composite particles leads to heating of the gold core and decomposition of surrounding matrix acting as temperature probe. Cavities inside the ZIF‐8 matrix are found on TEM images after irradiation. Their size is determined dependent on laser energy density and the generated heat at the gold core after absorption of a laser pulse approximated. The surrounding of the gold cores can be heated up to ZIF‐8 decomposition over a distance up to 60 nm. This represents a method to visualize heat transfer from the gold cores to the ZIF‐8 matrix in three dimensions. Studies on ZIF‐8 encapsulated Au@ZnO dot‐rod particles give insight in heat transfer between the particle components and show the applicability of the method to different, more complex systems. Abstract : Laser irradiation induced heating of plasmonic nanoparticles encapsulated in a ZIF‐8 matrix reveals the formation of cavities within up to 45 nm distance from their surface. Dependent on the used laser energy density, their size is tuneable. For irradiated heterostructures, heat transfer between their components can be visualized indirectly.